Over-segmentation of handwriting Arabic scripts using an efficient heuristic technique - Al Hamad, H. A. (2012 International Conference on Wavelet Analysis and Pattern Recognition, 2012)
As is well known, good segmentation is one reason for high accuracy of character recognition; this paper proposes and investigates a new technique for segmentation of handwritten Arabic scripts. A new Arabic heuristic segmenter (AHS) has been implemented. The AHS employs three new features to locate a Prospected Segmentation Point (PSP) based on shape of the word image, first, remove the punctuation marks (dots), second, ligature detection, and third, additional techniques. Remove the punctuation marks technique has been used to avoid the overlap of the ligature to decrease errors of "missed" and "bad" segmentation points. Ligature detection technique has been used to improve locate the segmentation points that calculated based on distance between local minima and maxima of histogram, the technique calculated based on the distance between foreground and background pixels of word image histogram. An additional technique that contains the average character width technique, and close/open holes detection technique has also been investigated to enhance the overall results of segmentation.